Manus Ex Machina: The Tactile Interface of Lady Audley’s Secret - Gagné, Ann (Australasian Journal of Victorian Studies, 2020)
This article argues that hands and their touch in Mary Elizabeth Braddon’s Lady Audley’s Secret create a narrative tactile interface that emphasizes how every contact leaves a trace. This ability to trace and provide continuity reinforces the forensic nature of the plot of the novel. By focusing on four specific aspects of tactility – reciprocal touch, touch within letter writing and distribution, tactility in negotiating environments in the novel and in stage adaptations, as well as ghostly touches – this article demonstrates that a hand from within the machine (a manus ex machina) guides the narrative. The domination of hands, as well as an emphasis on tactility, highlights a haptic form of interface that became part of a mid-to-late Victorian fascination with touch as a means to evoke morals, social boundaries, concepts of embodiment, and material confines.